The Impact of Music Activities on Foreign Language, English Learning for Young Children - Liza Lee; Shu-Chuan Lin (European Teacher Education Network, 2015)
The purpose of the study was to examine the impact of music activities on foreign language, English learning for children at age four. The methodology of the study used a quantitative analysis to measure validity based on assessment scales used in the observation forms by the observers and a qualitative study using interviews with classroom teachers and parents. A group of children at age four was selected by purposive sampling to participate in the study. The duration was 18 weeks with 45-minute instructional sessions twice per week. The teaching content included a Hello Song, Letter Song, Musical Storytelling, Music Appreciation, Musical Movement and Goodbye Song. The study applied the thematic music elements to the teaching content. The results were the following:1)Based on the comparison of pre- and post-test and observation forms, the quantitative scores for the participants were clearly enhanced; 2) Based on the observation forms, teacher's observation and parental reports, the use of the music, musical instruments and supplemental materials for the participants' foreign language, English learning were developed.